Bi-conical reflectance factor in contrasting vegetal species: global modeling - Paz Pellat, Fernando; Cano, Alejandro; Bolaños, Martín; Chávez, José; Marin, Ma. Isabel; Romero, Enrique (REVISTA TERRA LATINOAMERICANA, 2018)
Classification of vegetation using multi-angular spectral information has been approximated using restricted modeling schemes or with homogeneity or stationarity hypotheses. This paper presents a global modeling scheme of zenith and azimuthal angles in vegetation reflectance, extending the developments to the case of effects of changes on optical properties of vegetation substrates (soils) and plant density (foliage). This synthesis is performed in an upper space of compaction that depends essentially on two parameters and encompasses all the variations analyzed. The global modeling scheme developed was applied to the case of plant arrangements, different densities, of eight species with contrasting archetypes and bare soils. Modeling was applied to measurements of bi-conical reflectance factors, where adjustments were excellent (generally with R2 ≥ 0.99 and mean relative errors less than 7%). Analysis of the results showed that multi-angular spectral information for species classification under generalized conditions still has problems in discriminating species. This can be explained by the analysis synthesis of variations associated with discrimination.